Investigating the Relationship Between Structure, Ice Recrystallization Inhibition Activity and Cryopreservation Ability of Various Galactopyranose Derivatives - Tokarew, Jacqueline (Université d'Ottawa / University of Ottawa, 2011)
The goal of our research is to generate cryopreservation agents derived from antifreeze glycoproteins. One postulated mechanism of cell cryo-injury is ice recrystallization. It is known that simple saccharides and cryopreservation agents (DMSO) display ice recrystallization inhibition (IRI). This study assessed the cytotoxicity and cryopreservation ability of these sugars in relation to their IRI. It was determined that compounds with greater IRI have increased cytotoxicity yet confer cryoprotection. To further investigate how structure is affecting IRI activity, several galactopyranoside derivatives were synthesized. A series of deoxy and α-Callyl- deoxy galactopyranoses were prepared. Testing determined that removal of any hydroxyl group removes IRI. 3-deoxy-β-thiophenyl galactose was also synthesized and had surprisingly better IRI than β-thiophenylgalactose. Also, 6-azido galactose had similar IRI to 6-deoxy galactose. Lastly, a series of β- thioalkylgalactosides was synthesized and testing gave contradicting results which suggest that predicting IRI based on hydrophilicity is more complicated than initially hypothesized.
Keywords: cryopreservation; ice recrystallization; deoxy galactosides; thiophenylgalactose; azido galactosides; amino galactosides; cytotoxicity; antifreeze glycoproteins